Collaborative project-based learning enhances 4c skills in vocational fashion design students - Nanda Sari Siregar; Rahmiati Rahmiati; Weni Nelmira; M. Giatman; Armina Sari Harahap; Fadhillah Riski Aisyah Nasution; Alifah Biggum Nabila (Global Econedu, 2026)
This study aimed to examine the effectiveness of Collaborative Project-Based Learning (CPBL) in enhancing students' critical thinking, creativity, communication, and collaboration (4C) skills in the Children's Fashion Design course. A quantitative quasi-experimental study employing a posttest-only control group design was conducted with 40 vocational fashion design students, equally assigned to experimental and control groups. Data were collected using a validated structured observation instrument (Aiken's V = 0.868; item validity = 0.905) and analyzed through descriptive statistics, Shapiro–Wilk normality, Levene's homogeneity, and independent-samples t-tests. Students receiving CPBL achieved significantly higher scores in critical thinking (54.65 vs. 46.00), creativity (54.30 vs. 42.30), communication (54.40 vs. 41.80), collaboration (54.70 vs. 42.30), and overall 4C competence (218.05 vs. 172.40) than the control group (p < 0.001). CPBL effectively promotes integrated 4C competencies and represents an appropriate pedagogical approach for strengthening twenty-first-century skills in vocational fashion education